A novel dynamic stall model based on Theodorsen theory and its application. (June 2022) - Li, Zhiguo; Gao, Zhiying; Chen, Yongyan; Zhang, Liru; Wang, Jianwen
Abstract: The unsteady aerodynamic characteristics and serious time-lag of wind turbine blades due to long time of dynamic stall make the actual measured power of rotor seriously deviate from its static prediction value. Therefore, dynamic stall model is becoming more and more significant for the Megawatt wind turbine with larger size and flexibility. In this paper, a novel dynamic stall model accounting for attached flow and dynamic separation flow of trailing edge is built using Theodorsen theory and Kirchhoff potential flow theory. The model includes the unsteady effect arising from vortex shedding and flow separation on trailing edge, and takes boundary layer lag and pressure lag into consideration. A validation is carried out by comparing the response of the model with incompressible dynamic stall model in software GH Bladed using airfoils data from National Renewable Energy Laboratory (NREL) 5 MW offshore wind turbine blades as input. The consistent results prove that the proposed model is accurate, reliable and universal. Furthermore, effect factors such as mean angle of attack, angle of attack amplitude, Mach number, reduced frequency and time constants on dynamic stall performance are further explored. The proposed model will provide a new choice for calculating aerodynamic load of the blades under stall condition. Graphical abstract: Image 1